2010
DOI: 10.4314/sljbr.v2i1.56607
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Pathogens and Their Antimicrobial Susceptibility in Patients with Indwelling Urinary Catheter

Abstract: The indwelling urinary catheter (IUC) is the most significant risk factor for developing nosocomial urinary tract infections (UTIs). In order to determine the spectrum of bacterial etiology and antibiotic resistance pattern of uropathogens causing catheter associated UTI, a convenient sample size of ninety-two (92) patients on urethral catheter was investigated. Ethical approval for the study was obtained from the OAUTHC research and ethical committee. Catheter stream urine samples were obtained from all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
3
2
1
Order By: Relevance
“…The disparity may not be unconnected with the fact that their study participants were not on prolonged catheterization as the participants in this study. However, our work was in agreement with that of other workers [33], [34] but much lower than the findings of Taiwo and Aderounmu in 2006 [35], all of which were within the same geographic region. It is also interesting to note that in this study, Klebsiella spp (16.8%) was the most prevalent etiologic agent of CAUTI which is contrary to most of the earlier studies in which literature where E. coli appears to be the most prevalent agent [33], [36], [37] but it is consistent with the work of Panders et al in 2003 [38].…”
Section: Discussionsupporting
confidence: 90%
“…The disparity may not be unconnected with the fact that their study participants were not on prolonged catheterization as the participants in this study. However, our work was in agreement with that of other workers [33], [34] but much lower than the findings of Taiwo and Aderounmu in 2006 [35], all of which were within the same geographic region. It is also interesting to note that in this study, Klebsiella spp (16.8%) was the most prevalent etiologic agent of CAUTI which is contrary to most of the earlier studies in which literature where E. coli appears to be the most prevalent agent [33], [36], [37] but it is consistent with the work of Panders et al in 2003 [38].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, catheterization for seven or more days was identified as a risk factor for development of bacteriuria among urinary catheterized inpatients of JUMC. Similar findings have been reported in various countries around the world [23, 31, 34, 4551] including Ethiopia [32]. This may be because the longer time the catheter remains in the urinary system, it is highly likely bacteria can colonize, accumulates in the residual urine in the bladder, adhere or aggregate, and form complex communities of bacterial species called biofilms [11, 20].…”
Section: Discussionsupporting
confidence: 76%
“…Cotrimoxazole (20), Arbaminch, Ethiopia (16.8%) (11), China(15.8%) (21), Uganda (15.3%) (22), Sudan 16.4% (23), and Chhattisgarh, India (10.6%) (24). Our finding is lower than studies conducted in India 42.9% (25), and Nigeria 60.9% (26). The variation could be due difference in sociodemographic characteristics, infection prevention policies, duration of catheterization, and immunological status of participants.…”
Section: Ciprofloxacincontrasting
confidence: 86%